2004
DOI: 10.1002/chem.200400663
|View full text |Cite
|
Sign up to set email alerts
|

Topological Analysis of Electron Densities: Is the Presence of an Atomic Interaction Line in an Equilibrium Geometry a Sufficient Condition for the Existence of a Chemical Bond?

Abstract: The structure, energetics, and electron density in the inclusion complex of He in adamantane, C10H16, have been studied by density functional theory calculations at the B3LYP6-311++G(2p,2d) level. Topological analysis of the electron density shows that the He atom is connected to the four tertiary tC atoms in the cage by atomic interaction lines with (3,-1) critical points. The calculated dissociation energy of the complex He@adamantane(g)=adamantane(g) + He(g) of DeltaE=-645 kJ mol(-1) nevertheless shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 42 publications
5
133
0
Order By: Relevance
“…Apparently, Poater, Solà, and Bickelhaupt and others that they refer to such as Cioslowski [42] and Haaland, [43] have the ability to distinguish between interactions that are indistinguishable by physics alone. They simply "know" that in some cases a bond path implies bonding, while in others it implies the existence of repulsive forces, even though no net forces are present.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apparently, Poater, Solà, and Bickelhaupt and others that they refer to such as Cioslowski [42] and Haaland, [43] have the ability to distinguish between interactions that are indistinguishable by physics alone. They simply "know" that in some cases a bond path implies bonding, while in others it implies the existence of repulsive forces, even though no net forces are present.…”
Section: Discussionmentioning
confidence: 97%
“…[45] If the ClÀCl "nonbonded" interactions were indeed repulsive, solid chlorine could not exist! Haaland et al [43] question the presence of bond paths found to link the He and t C atoms in the He@adamantane inclusion complex, interactions that they describe as "strongly antibonding". The QTAIM analysis of such inclusion complexes indicates that, as anticipated for an equilibrium structure, there are no Feynman forces exerted on the nuclei and that in addition, the Ehrenfest force acting on the He j C surface is attractive, drawing the two atoms together.…”
Section: Discussionmentioning
confidence: 98%
“…It is hardly straightforward, therefore, to tell whether a computed bond path denotes the presence of a real bond or is simply an artifact of the topological analysis. [27][28][29][30] Further, the Laplacian (5 2 1(r)) map ( Figure 4) shows that this scalar field is positive (solid lines) over the entire region of the He-He and He-C interactions, with a tiny distortion in the charge depletion area along the connecting path between the helium atoms, suggesting that the He-X (X = C, He) interactions result from the contact of closed-shell fragments. The properties of 1(r) at the associated (3,À1) critical points reflect key characteristics associated with weak intermolecular interactions: a low value for 1 He-X and 5 2 1(r) > 0 (Figure 4).…”
Section: Geometries and Energiesmentioning
confidence: 95%
“…[60] We calculated in particular the MP2A C H T U N G T R E N N U N G (full)/6-311 + + GA C H T U N G T R E N N U N G (2d,2p)/SDD charge density 1 and the Laplacian of the charge density 5 2 1 at the bond critical points (bcp), intended as points on the attractor interaction lines where 51 = 0 (for a discussion about bond paths and chemical bonds see refs. [61][62][63][64][65][66]). …”
Section: Computational Detailsmentioning
confidence: 99%